COMPUTER TRAINING AS A LEARNING SUPPLEMENT PAKET C IN PKBM SAUDARA SEJIWA DISTRICT OF DAYEUHKOLOT - Aneu Liana Dewi (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
The background of conducting this research is the need to strengthen the attractiveness of learning thatcan foster the learning appeal of PKBM Saudara Sejiwa in learning Paket C. The purpose of this studywas to find out how computer training as a supplement to Paket C learning in the PKBM SaudaraSejiwa. The theoretical study used is the theory of out-of-school education, PKBM theory, equalitytheory, training theory, and learning theory. Researchers used qualitative descriptive methods tointerview and observation techniques to obtain information from informants. The researcher took arandom sample of one PKBM manager on the grounds that the manager's role affected the conditionsin PKBM, one PKBM tutor, and three PKBM students PKBM Saudara Sejiwa because tutors andlearners were directly involved in the computer learning process. The results of the research at PKBMSaudara Sejiwa is that computer training as a supplement to learning the Paket C of PKBM SaudaraSejiwa has been running well, seen from the benefits and encouragement of students to participate intraining activities, although constrained by the division of time between training and student work.Conclusion This study is that computer training as a supplement to Paket C learning at PKBM SaudaraSejiwa has been running as it should or according to the needs of students. Seen from the number ofgraduates who are unemployed. Computer training is a good learning supplement because, computertraining is part of the process of learning and the principles of training are developed into learning forPaket C students at the PKBM Saudara Sejiwa.